2010
DOI: 10.2147/hmer.s13796
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum HBsAg level, HBV DNA level, and peripheral immune cells in patients with chronic hepatitis B virus infection

Abstract: BackgroundThe chronicity of hepatitis B virus (HBV) infection is attributed to inappropriate functioning of cell-mediated immunity. Besides the importance of measuring serum HBV DNA and HBV surface antigen (HBsAg) as markers of viral replication and exposure, respectively, studies regarding their influence on immune cell status in chronic HBV infection are still scarce. Because such studies of chronic HBV patients have not been reported for India, we attempted to evaluate the relationship between serum concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
3
10
2
Order By: Relevance
“…This was similar to results of studies carried in Cameroon by Tufon et al [16] and can be attributed to cell mediated liver cell damage and not cytopathic effect of the virus [22]. From this study mean values of AST (106.7U/L) and (60.7 U/L) were higher in both HBV positive and negative subjects compared to ALT (76.96 U/L) and (37.61 U/L) respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This was similar to results of studies carried in Cameroon by Tufon et al [16] and can be attributed to cell mediated liver cell damage and not cytopathic effect of the virus [22]. From this study mean values of AST (106.7U/L) and (60.7 U/L) were higher in both HBV positive and negative subjects compared to ALT (76.96 U/L) and (37.61 U/L) respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Keeping in mind the reported findings of immune stimulatory effects of HBV towards other cells of the immune system, such as Kupffer cells in liver (Hosel, 2009), the significant drop in the mRNA expression of both RANTES and IP-10 as observed in our group of cirrhotic subjects might have insinuations in promoting lesser recruitment of immunocompetent cells from peripheral pool to liver to avert further damage. This conjecture can be conjured up to our earlier finding of significant suppression of CD8 T cells in CHB subjects without any numerical increment in the T helper (CD4) or NK cell populations (Mukherjee, 2010). Of note , Crawford et al (2011) reported a significant reduction in CD8 T cell numbers and function in the absence of RANTES in chronic viral infection while the CD4 T cells remain unaffected in such situation.…”
mentioning
confidence: 56%
“…For expression of data, HBsAg concentrations obtained in ng/mL were converted to IU/mL, considering that 0.15 ng/mL of HBsAg is equivalent to 350 IU/ml as mentioned before (Biswas, 2003;Mukherjee, 2010).…”
Section: Quantitation Of Serum Hbsagmentioning
confidence: 99%
“…The liver injury in hepatitis B is the result of cell mediated hepatic injury rather than cyopathic effect of the virus. 16 A higher percentage (85.66%) of patients showed normal AST level that could be explained by mild injury of liver hepatocytes. 17 Generally, ALT and AST are recognized markers for liver diseases.…”
Section: Discussionmentioning
confidence: 96%